2021
DOI: 10.1002/adfm.202102838
|View full text |Cite
|
Sign up to set email alerts
|

Realizing High Thermoelectric Performance in Earth‐Abundant Bi2S3 Bulk Materials via Halogen Acid Modulation

Abstract: Bi2S3‐based thermoelectric materials without toxic and expensive elements have a high Seebeck coefficient and intrinsic low thermal conductivity. However, Bi2S3 suffers from low electrical conductivity, which makes it a less‐than‐perfect thermoelectric material. In this work, halogen elements F, Cl, and Br from halogen acid are successfully introduced into the Bi2S3 lattice using a hydrothermal procedure to efficiently improve the carrier concentration. Compared with the pure sample, the electron concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 43 publications
2
38
0
Order By: Relevance
“…[3] Since the discovery of the Seebeck effect in 1821, there have been sustained efforts to increase the maximum thermoelectric conversion efficiency η max . [4][5][6]…”
mentioning
confidence: 99%
“…[3] Since the discovery of the Seebeck effect in 1821, there have been sustained efforts to increase the maximum thermoelectric conversion efficiency η max . [4][5][6]…”
mentioning
confidence: 99%
“…is the Planck constant and m* is the DOS effective mass at the Fermi level. 12 The obtained m* of Bi 2 S 3 with BSBr addition was higher than that of pure Bi 2 S 3 , and the results are shown in Table 1. sS 2 was calculated using the measured high s and S values, and the results are shown in Fig.…”
Section: Resultsmentioning
confidence: 87%
“…To date, strategies for optimizing the TE properties of Bi 2 S 3 have mainly focused on improving its s. It is reported that doping and alloying with appropriate elements are effective for improving the electrical transport properties of Bi 2 S 3 . 12,17,19 Both experiments 12,20 and first-principles calculations 21 have confirmed that Br doping is very helpful for achieving good electrical transport properties in Bi 2 S 3 . However, it is difficult to directly realize Br doping because Br 2 is a liquid and BiBr 3 is prone to hydrolysis to BiOBr during hydrothermal processing.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, the scarcity of Te, with an abundance in the Earth's crust of around 0.001 ppm, may restrict their wide applications. Considering the signicantly high earth abundance of sulfur (S) of around 350 ppm, S-based materials, including Bi 2 S 3 , 37,38 PbS, 39,40 Cu 2 S, 41,42 and CuFeS 2 , 43,44 have received intensive interest for the replacement of their Te-based counterparts. Due to their increased ionic bonding strength, Sbased materials for thermoelectric applications are prone to exhibiting both low s and PF as a consequence of low charge carrier mobility, m H .…”
Section: Introductionmentioning
confidence: 99%